Effects of L-Carnitine Supplemented Throughout all Grow-Finish Phases or Only in Late Finishing on Growth Performance and Carcass Characteristics of Pigs - Jamil E. G. Faccin; Mike D. Tokach; Joel M. DeRouchey; Jordan T. Gebhardt; Robert D. Goodband; Jason C. Woodworth (Kansas Agricultural Experiment Station Research Reports, 2022)
A total of 1,833 mixed-sex growing-finishing pigs (PIC, 337 × 1050; initially 58.5 ± 1.62 lb) were used in a 112-d growth trial to determine the effects of adding L-Carnitine throughout the entire grow-finishing period or for just the last 28 d before marketing on growth performance and carcass characteristics. There were 26 replicate pens per treatment and 20 (group 1) or 27 (group 2) pigs per pen in a completely randomized design. There were three treatment diets: 1) control with no added L-Carnitine; 2) diets containing 50 ppm of L-Carnitine for the entire trial; and 3) control diet until d 84 and then a diet containing 50 ppm of L-Carnitine. On day 84, half of the control pens were randomly assigned to the diet containing 50 ppm of L-Carnitine. The experimental diets were corn-soybean meal-DDGS-based and were fed in 4 phases. From d 0 to 84, statistical analyses compared the 52 pens of pigs fed the control diets to the 26 pens of pigs that were fed diets with L-Carnitine. From d 85 until market, comparisons were made using all 3 treatments. In the first 28 d, pigs fed L-Carnitine had greater (P<0.002) BW, ADG, and ADFI and similar F/G (P= 0.459) as those fed the control diet. No evidence for differences (P>0.13) were observed in growth performance from d 29 to 56 and from d 57 to 84. From d 0 to 84, pigs fed L-Carnitine had a tendency (P= 0.052) for greater ADFI, but there was no evidence (P>0.14) of differences for ADG, F/G, removals, and mortalities. From d 85 to market and overall, there was no evidence of differences (P>0.22) for ADG, ADFI, F/G, or removals and mortalities. For carcass traits, no difference (P>0.54) in HCW, yield, backfat, lean, and loin depth were detected between treatments. In conclusion, added L-Carnitine improved performance in the early grow-finishing phase, but due to greater variation, this statistical difference did not last until market, resulting in the same overall performance. Feeding L-Carnitine only for the last 28 d also did not elicit growth and carcass improvements.
Keywords: carcass characteristics; feed additive; growth; L-Carnitine; swine